Effectiveness of mosquito trap with sugar fermentation solution attractant in mosquito control - Mely Gustina; Yuli Agustina; Agus Widada (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Dengue Hemorrhagic Fever (DHF) is a diseaase caused by the bite of the Aedes Aegypti mosquito which is infected with the dengue virus. The way to control the mosquito population is by using mosquito traps with attaractant media. Purpose: To evaluate the effectiveness of a granulated sugar fermentation solution as an attractant for controlling mosquitoes. Method: A experimental approach, specially focusing on Posttest Only Control Group Design. The study took place from March to June 2024, in Penurunan Village, Bengkulu. The independent variable was type of attractant in mosquito traps while the dependent variables is number of trapped mosquitoes. The analysis proceeded with a univariate test to determine the frequency distribution of characteristics mosquito trap, followed by bivariate analysis using one way anova dan bonferroni test with the single-blind innovation method. All analyses were conducted using SPSS 24. Results: The results showed the number of mosquito larvae with fermented bait at 25% concentration was 64 larvae, at 35% concentration was 154 larvae, at 45% concentration was 141 larvae, and in the control group was 9 larvae. The total number of larvae obtained was 368 larvae. One Way Anova test showed a significant difference with a p value = 0.001 (<0.05). Conclusion: Fermented sugar solution with concentrations of 25%, 35%, 45% is effective as an attractant to protect mosquitoes.